Autorrrrrr
Vă rog mult
![Autorrrrrr Vă Rog Mult class=](https://ro-static.z-dn.net/files/ddc/98cddd309aae3cbb936ce01f822d3f1e.jpg)
Explicație pas cu pas:
[tex]$\mathbf{ \frac{1}{x + 1} - \frac{3x}{x - 1 } = ? }$[/tex]
[tex]$\mathbf{ \frac{x - 1}{(x + 1)(x - 1)} - \frac{(x + 1) \times 3x}{(x + 1)(x - 1)}\longrightarrow \: = \frac{x - 1 - 3x \times(x + 1) }{(x + 1)(x - 1)} }$[/tex]
[tex]$\mathbf{ \frac{x - 1 - 3x {}^{2} - 3x}{ {x}^{2} - 1}\longrightarrow \: = \: \frac{ - 2x - 1 - {3x}^{2} }{ {x }^{2 } - 1 } }$[/tex]
[tex]$\mathbf{ \frac{ - {3x}^{2} - 2x - 1}{ {x}^{2} - 1} }$[/tex]
Am folosit formula : (a-b)(a+b)=a²-b²
Bafta!